Advanced microstructure, morphology and CO gas sensor properties of Cu/Ni bilayers at nanoscale - Ghaderi, Atefeh; Shafiekhani, Azizollah; Solaymani, Shahram; Ţălu, Ştefan; da Fonseca Filho, Henrique Duarte; Ferreira, Nilson S.; Matos, Robert Saraiva; Zahrabi, Hadi; Dejam, Laya (Scientific reports, 2022)
In this study, we investigated the morphology of synthesized Cu/Ni nanoparticles in trace of carbon sources by the co-deposition process of RF sputtering and RF-PECVD methods and localized surface plasmon resonance of CO gas sensing of Cu/Ni nanoparticles. The surface morphology was studied by analyzing 3D micrographs of atomic force microscopy using image processing techniques and fractal/multifractal analyses. The MountainsMap® Premium software with the two-way ANOVA (Variance analysis) and least-significant differences tests were used for statistical analysis. The surface nano-patterns have a local and global particular distribution. Experimental and simulated Rutherford backscattering spectra confirm the quality of nanoparticles. Then, prepared samples were exposed to CO gas flue to study their gas sensor application using the localized surface plasmon resonance method. Increasing the Ni layer over Cu one shows an interesting result in both morphology and gas sensing sides. Advanced stereometric analyses for the surface topography of thin films in conjunction with Rutherford backscattering spectrometry and Spectroscopic analysis make a unique study in the field.